2022
DOI: 10.1038/s41598-022-13174-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of FXI activity with thrombo-inflammation, extracellular matrix, lipid metabolism and apoptosis in venous thrombosis

Abstract: Animal experiments and early phase human trials suggest that inhibition of factor XIa (FXIa) safely prevents venous thromboembolism (VTE), and specific murine models of sepsis have shown potential efficacy in alleviating cytokine storm. These latter findings support the role of FXI beyond coagulation. Here, we combine targeted proteomics, machine learning and bioinformatics, to discover associations between FXI activity (FXI:C) and the plasma protein profile of patients with VTE. FXI:C was measured with a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…Higher levels of leptin were associated with higher levels of fibrinogen and plasminogen activator inhibitor‐1 in persons with an unhealthy metabolic profile 70 . In a similar scope, the close relation between coagulation and inflammation was further evaluated by Pallares Robles et al, who showed an interesting interaction between FXI activity and thrombo‐inflammation and lipid metabolism 71 …”
Section: Isth Congress Reportmentioning
confidence: 83%
“…Higher levels of leptin were associated with higher levels of fibrinogen and plasminogen activator inhibitor‐1 in persons with an unhealthy metabolic profile 70 . In a similar scope, the close relation between coagulation and inflammation was further evaluated by Pallares Robles et al, who showed an interesting interaction between FXI activity and thrombo‐inflammation and lipid metabolism 71 …”
Section: Isth Congress Reportmentioning
confidence: 83%
“…107 This clinical observation is echoed by recent proteomics analyses of plasma from patients presenting with a venous thromboembolism (VTE). 108 These analyses show that more than 80 proteins were associated with FXI coagulation activity (FXI:C) both during the acute VTE event and in the 12 months following the event. The FXI-related proteins identified were involved in immune pathways, extracellular matrix interaction, lipid metabolism, and apoptosis.…”
Section: Fxia Substrates That Regulate Inflammationmentioning
confidence: 86%
“…Elevated total and LDL cholesterol levels were associated with increased FXI activity [38] whereas the use of lipid-lowering drugs resulted in decreased levels of FXI [39][40][41]. Proteomics analysis indicated associations between proteins involved in lipid metabolism and FXI activity in patients with VTE at 12 months follow-up [42]. Lowering FXI activity was associated with improved fibrin clot permeability, which indicated increased susceptibility to clot lysis in coronary artery disease [41].…”
Section: Directionmentioning
confidence: 99%